Rest all things will be the same as the above program. Only the logic will change. Here, we are assigning x with the value x + y which means x will have a sum of both x and y.

Then, we are assigning y with the value x – y which means we are subtracting the value of y from the sum of (x + y). Till here, x still has the sum of both x and y. But y has the value of x.

Finally, in the third step, we are assigning x with the value x – y which means we are subtracting y (which has the value of x) from the total (x + y). This will assign x with the value of y and vice versa.

`1` | `import` `java.util.Scanner;` |

`2` | ` ` |

`3` | `class` `SwapTwoNumberWithoutThirdVariable` |

`4` | `{` |

`5` | ` ` `public` `static` `void` `main(String args[])` |

`6` | ` ` `{` |

`7` | ` ` `int` `x, y;` |

`8` | ` ` `System.out.println(` `"Enter x and y"` `);` |

`9` | ` ` `Scanner in = ` `new` `Scanner(System.in);` |

`10` | ` ` |

`11` | ` ` `x = in.nextInt();` |

`12` | ` ` `y = in.nextInt();` |

`13` | ` ` |

`14` | ` ` `System.out.println(` `"Before Swapping\nx = "` `+x+` `"\ny = "` `+y);` |

`15` | ` ` |

`16` | ` ` `x = x + y;` |

`17` | ` ` `y = x - y;` |

`18` | ` ` `x = x - y;` |

`19` | ` ` |

`20` | ` ` `System.out.println(` `"After Swapping without third variable\nx = "` `+x+` `"\ny = "` `+y);` |

`21` | ` ` `}` |

`22` | `}` |

Output:

Enter x and y

45

98

Before Swapping

x = 45

y = 98

After Swapping without a third variable

x = 98

y = 45

45

98

Before Swapping

x = 45

y = 98

After Swapping without a third variable

x = 98

y = 45

## Comments